Climat des magasins : vers de nouvelles consignes conciliant développement durable et conservation ? - Thi Phuong Nguyen (In Situ)
The new building of the national library of France (BnF François Mitterrand) was designed in the early 90’s, when the concepts of sustainable development and energy savings were not as pregnant as today. It is a very high energy consumer building. Since 2008, these new economical aspects have been reconsidered and environmental conditions/cost simulations were done. Actions were implemented to reduce the energy consumption induced by the air conditioning of the repositories, provided they do not affect the good preservation of the collections, which remains the priority.